Bite's Borneo - Lubiren, Malorrida; Jos, Ezra Artahsasta; Kagiah, Kerrin; Abdul Rahman, Farhana Izzati; Saili, Mohd Hamdi; Gerry, Mohd Syahrizan (2015)
Traditional food is a business that deals with variety traditional food in Sabah. We are the first company that serve traditional food all over Sabah. We are proud to serve our traditional food as to deliver excellent service and as a way to promote Sabahan's culture. We are very strict and meticulous in our ingredient selection. We are only take fresh ingredient. The name of 'Bite's Borneo' comes from the Borneo people which always eat traditional food. Customers can choose variety type of traditional food such as Tuhau, Bambangan Bosou, Ampap, Hinava and Ambuyat. However, the most popular menu which customers should try was Hinava, which is the raw fishes sliced into thin pieces. The location for our outlet is at Tanjung Aru Beach 1. From the location chosen, we believe that it is a strategic place to attract customers which we are targeting foreign people, local people, teenagers and working people that can enjoy their 'traditional food'. The uniqueness of our product may bring satisfactions, happiness, and j oy to customer. We also come out with other alternatives to serve it with attractive packaging, variety of delicious flavours, condition of the outlet and the customer service provide by our staff.